1999
DOI: 10.1007/s004410051367
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and synaptic connectivity of nitric oxide synthase-immunoreactive neurons in the guinea pig retina

Abstract: Immunocytochemical methods with an antiserum against neuronal nitric oxide synthase (NOS) were applied to identify the morphology and synaptic connectivity of NOS-like immunoreactive neurons in the guinea pig retina. In the present study, two types of amacrine cells were labeled with anti-NOS antisera. Type 1 cells had large somata located in the inner nuclear layer (INL) with long, sparsely branched processes ramifying mainly in stratum 3 of the inner plexiform layer (IPL). The somata of type 2 cells (smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…αGCs have been reported to couple with both αGCs and ACs (Pang et al 2003; Hidaka et al, 2004; Schubert et al, 2005). Beside gap junctions, NOACs also make chemical synapses onto other ACs and GCs (Oh et al 1999). These chemical synapses are expected to be GABAergic (Kim IB, et al, 1999) and nitric oxidergic; but how the NO release is modulated by presynaptic events is mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…αGCs have been reported to couple with both αGCs and ACs (Pang et al 2003; Hidaka et al, 2004; Schubert et al, 2005). Beside gap junctions, NOACs also make chemical synapses onto other ACs and GCs (Oh et al 1999). These chemical synapses are expected to be GABAergic (Kim IB, et al, 1999) and nitric oxidergic; but how the NO release is modulated by presynaptic events is mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ultrastructure of the somas and staining intensity, NOACs were generally classified into two major types in earlier reports (Oh et al, 1999; Kim et al, 2000), namely type I and type II. The type I cells have large extensively stained somas, while type II cells posses small and weakly stained somas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoreactivity for nNOS in the guinea pig retina has been reported in detail by Oh et al (1999). They found that nNOS-labeled cells were distributed sparsely throughout the retina.…”
Section: Guinea Pigmentioning
confidence: 92%
“…This assumption has been corroborated by the fact that NADPH-d is colocalized with NOS in several neuronal systems Perez et al, 1995) and also by the fact that an NADPH-d reaction is not detected in the retinae of mice devoid of the neuronal NOS gene (Darius et al, 1995). Thus, NADPH-d histochemistry (Sandell, 1985;Sagar, 1986Sagar, , 1990Mü ller et al, 1988;Cobcroft et al, 1989;Mitrofanis, 1989;Osborne et al, 1993;Lau et al, 1994) and immunocytochemical methods using anti-NOS antisera Koistinaho et al, 1993;Yamamoto et al, 1993;Oh et al, 1998Oh et al, , 1999Chun et al, 1999;Kim et al, 1999) have been applied to study the morphology and topographical distribution of NOS cells in the mammalian retina.…”
Section: Introductionmentioning
confidence: 89%